Sediment Transport and Economic Social Effect of Bowone People Mining Sangihe Islands Regency - Kumaseh, Eunike Irene; Sarapil, Costantein Imanuel; Ikhtiagung, Ganjar Ndaru (Sam Ratulangi University, 2023)
This study aims to determine the magnitude of the sedimentation rate and the prediction of sediment transport in Binebas Bay as the scope of the Bowone people's mine run-off disposal area, as well as the socio-economic impacts on the community and especially for fishermen. Sediment diameter measurements were carried out by taking sediment samples at each station using a sediment trap. Sediment traps made of pipes will be installed at each station and the height of the sediment will be measured using a ruler every 2 weeks for 3 months. The research data were analyzed using the comparative method, namely the results of measuring the sediment rate in the field compared to the calculation results according to Engelund. The sediment rate in the waters of Binebas Bay which is close to the people's mining in Bowone Village is 0,058943 m3/year. Sediment transport in the waters of Binebas Bay is m3/m*s. Sedimentation is still relatively low (small) in the waters of Binebas Bay. Socially, people's mining activities in Kampung Bowone have a positive impact where there is the availability of employment opportunities for the community. Economically, people's mining activities increase people's income. However, the negative impact is environmental damage. Keywords: sediment transport; socio-economic impact; people's mine; Bowone village; Sangihe Islands Abstrak Penelitian ini bertujuan untuk mengetahui besarnya laju sedimentasi dan prediksi transport sedimen di Teluk Binebas sebagai lingkup wilayah buangan run-off tambang rakyat Bowone, serta dampak sosial ekonomi bagi masyarakat dan khususnya bagi nelayan. Diameter sedimen diukur dengan mengambil sampel di tiap Stasiun. Perangkap sedimen dibuat dari pipa dan diukur tinggi sedimennya tiap 2 minggu selama 3 bulan. Data penelitian dianalisis kemudian dilakukan komparasi antara hasil pengukuran laju sedimentasi di lapangan dengan hasil perhitungan transportasi sedimen menurut Metode Engelund. Laju sedimen di perairan Teluk Binebas yang dekat dengan pertambangan rakyat Kampung Bowone yaitu sebesar 0,058943 m3/ tahun. Transpor sedimen di perairan Teluk Binebas yaitu m3/m*s. Sedimentasi masih tergolong rendah (kecil) di perairan Teluk Binebas. Secara sosial, kegiatan pertambangan rakyat di Kampung Bowone memberikan dampak yang positif dimana terdapat ketersediaan lapangan kerja bagi masyarakat. Secara ekonomi, kegiatan pertambangan rakyat meningkatkan pendapatan masyarakat. Namun, dampak negatifnya adalah kerusakan lingkungan. Kata kunci: transport sedimen; dampak sosial ekonomi; tambang rakyat; kampung bowone; kepulauan sangihe